Why opportunities matter more than challenges: Lessons from Korean SMEs’ export strategies - Lee, Byungki; Yin, Wenyan; Ivan, Ureta Vaquero (Edelweiss Applied Science and Technology, 2025)
This study examines why opportunities play a more decisive role than challenges in shaping the export strategies and performance of Korean SMEs, using the SCOPE framework. Focusing on four key components—strategy, challenge, opportunity, and export—within the SCOPE framework, the study investigates how external challenges and opportunities influence SMEs’ strategy adoption and export outcomes. Additionally, it explores the moderating role of foreign direct investment (FDI). Data were collected through a structured online survey, yielding 500 valid responses from SMEs across diverse industries in South Korea. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) reveal that challenges exert no significant influence on strategy adoption, whereas opportunities have a strong positive effect. Strategies mediate the relationship between opportunities and export performance, while FDI further reinforces this effect, particularly by enhancing strategic export outcomes that contribute to long-term performance. By applying the SCOPE framework, this research offers both theoretical contributions to SME internationalization and practical implications for managers and policymakers aiming to strengthen SMEs’ global competitiveness through an opportunity-focused approach.